Prolegomena to a philosophy of religion - Schellenberg, J. L., 1959- (Cornell University Press, 2005)
"There is no attempt here to lay down as inviolable or to legislate certain ways of looking at things or ways of proceeding for philosophers of religion, only proposals for how to deal with a range of basic issues-proposals that I hope will ignite much fruitful discussion and which, in any case, I shall take as a basis for my own ongoing work in the field."--The PrefaceProviding an original and systematic treatment of foundational issues in philosophy of religion, J.L. Schellenberg's new book addresses the structure of religious and irreligious belief, the varieties of religious skepticism, and the nature of religion itself. From the author's searching analysis of faith emerges a novel understanding of propositional faith as requiring the absence of belief. Schellenberg asks what the aims of the field should be, setting out a series of principles for carrying out some of the most important of these aims. His account of justification considers not only belief but also other responses to religious claims and distinguishes the justification of responses, propositions, and persons. Throughout Prolegomena to a Philosophy of Religion, Schellenberg is laying the groundwork for an elaboration of his own vision while at the same time suggesting how philosophers might rethink assumptions guiding most of today's work in analytic philosophy of religion.